PENINGKATAN KEMAMPUAN MEMBACA AL-QUR’AN MELALUI METODE TAHSIN - Sholehah, Martus; Ridwan, Ahmad; Rukayyah, Siti (Al Jabiri: Jurnal Ilmiah Studi Islam, 2022)
Reading the Qur'an properly and correctly is an obligation for all Muslims. This is intended so that the verses of the Qur'an that are recited are in accordance with the reading of the Qur'an by the Prophet Muhammad, and so that they are in accordance with the intent and purpose of the verses of the Al-Qur'an itself. One of the ways to read the Qur'an properly and correctly is to learn the rules of tajwid and take tahsin with a teacher or someone who is an expert in that field, especially someone whose reading has been in sanad and has received a diploma to teach it again